Morphological and certain economic traits under rural conditions of local ducks of Kashmir - BIHAQI, SYED FAHEEM AHMAD; BHAT, G A; GANAI, T A S; BIHAQI, SYED JUNAID; HAMADANI, HENNA (The Indian Journal of Animal Sciences, 2014)
The present study was aimed at characterizing the local ducks of Kashmir Valley. The overall average adult body weight of the adult ducks was 1.70±0.01 kg. The highest average body weight of 1.72±0.01 kg was found in the ducks of district Bandipora and followed by 1.70±0.02 kg and 1.69±0.02 kg in ducks of Budgam and Ganderbal respectively. Males were heavier than females, with 1.62±0.01 kg weight. Four types of bill colors, viz. greenish black (mosaic), pinkish black, yellow and greenish yellow mosaic, were observed. Yellow was predominant with frequency of about 74%. Four types of bean colors were observed viz. black, pink, white and yellow with preponderance of black (96%). There was equal distribution of grey and brown eye colors while as 99% shanks were orange colored and only 1% had orange with black patches on it. Egg analysis of 305 eggs from three districts revealed green and white shell colors. The overall weight of the eggs was recorded to be 66.20±0.42 g with Ganderbal district having the highest egg weight of 69.19±0.80 g and Budgam with the least of 62.10±0.46 g. Haugh unit score was 69.37±0.43 and the highest score was recorded in the eggs from Ganderbal district (70.58±0.71).